Utilization of Learning Videos Using Canva Application - Edward Gland Tetelepta; Ferdinand Salomo Leuwol; Taty Hernawaty; Rahyu Setiani (P3M IAI Nusantara Batang Hari, 2023)
This article is useful to recognize how maximal learning using software-based tools (canva) and increase the knowledge of students at SD IT Masjid Raya Lantai Batu. Covid 19 requires schools to implement online-style learning as a result requiring elementary students to utilize digital applications to be a sense to help students in using presentation frames, concept maps, placards, and others. Activity applications using the Canva application can be directly applied and practiced in elementary schools because the application is cheap and also attractive. Canva is software that can be used by teachers to create interesting teaching materials. The purpose of this activity is to improve teachers' ability to be creative in shaping teaching materials using the canva application. The results of making learning videos using the canva application for class v SD IT Masjid Raya Batu Floor gave many positive effects, this can be shown from the results of making learning videos using the Canva application and none of the students gave a negative impression. Keywords: Canva, Elementary School, Learning.